Rifaximin Improves Clostridium difficile Toxin A-Induced Toxicity in Caco-2 Cells by the PXR-Dependent TLR4/MyD88/NF-κB Pathway - Esposito, Giuseppe; Nobile, Nicola; Gigli, Stefano; Seguella, Luisa; Pesce, Marcella; d’Alessandro, Alessandra; Bruzzese, Eugenia; Capoccia, Elena; Steardo, Luca; Cuomo, Rosario; Sarnelli, Giovanni (Frontiers in Pharmacology, 2016)
Background: Clostridium difficile infections (CDIs) caused by Clostridium difficile toxin A (TcdA) lead to severe ulceration, inflammation and bleeding of the colon, and are difficult to treat. Aim: The study aimed to evaluate the effect of rifaximin on TcdA-induced apoptosis in intestinal epithelial cells and investigate the role of PXR in its mechanism of action. Methods: Caco-2 cells were incubated with TcdA and treated with rifaximin (0.1−10 µM) with or without ketoconazole (10 µM). The transepithelial electrical resistance (TEER) and viability of the treated cells was determined. Also, the expression of zona occludens-1 (ZO-1), toll-like receptor 4 (TLR4), Bcl-2-associated X protein (Bax), transforming growth factor-β-activated kinase-1 (TAK1), myeloid differentiation factor 88 (MyD88) and nuclear factor-kappaB (NF-κB) was determined. Results Rifaximin treatment (0.1, 1.0 and 10 µM) caused a significant and concentration-dependent increase in the TEER of Caco-2 cells (360%, 480% and 680% vs TcdA treatment) 24 hours after the treatment and improved their viability (61%, 79% and 105%). Treatment also concentration-dependently decreased the expression of Bax protein (–29%, –65% and –77%) and increased the expression of ZO-1 (25%, 54% and 87%) and occludin (71%, 114% and 262%) versus TcdA treatment. The expression of TLR4 (–33%, –50% and –75%), MyD88 (–29%, –60% and –81%) and TAK1 (–37%, –63% and –79%) were also reduced with rifaximin versus TcdA treatment. Ketoconazole treatment inhibited these effects. Conclusions: Rifaximin improved TcdA-induced toxicity in Caco-2 cells by the PXR-dependent TLR4/MyD88/NF-κB pathway mechanism, and may be useful in the treatment of CDIs.